Evaluation of Mortality Rates for Children under the Age Group (1-3) Years in Babil Governorate for (2010-2017) by Using Linear Regression Model (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The phenomenon of child mortality is one of the most important societal phenomena that have been studied, evaluated and evaluated by a large number of statisticians and academic researchers, as well as by international health organizations that concern children in particular and the health of society in general[1]. This phenomenon has witnessed changes in rates over the past decades due to several related conditions such as lack of health awareness, health care programs, family health and others. Undernourishment, wars, migration, fertility, epidemics, etc. are all factors that can contribute to the growth of child mortality, especially those under five years of age [9] [10]. In recent years, globally, there has been significant progress in reducing child mortality rates for the under-5 population, falling to 5.6 (6.0, 6.0) million in 2016 from 12.6 (12.4, 12.8) in 1990. It has reached 15,000 deaths On the day of 2016, compared with 35,000 deaths per day in 1990. Approximately 39-44 deaths per 1000 live births in 2016, up from 92-95 per 1,000 live births in 1990. The neonatal mortality rate was 49% lower in 2016 than in 1990. Half of all child deaths in the world are represented by the Republics: India, Pakistan, Nigeria, Democratic Republic of the Congo and Ethiopia. In Iraq, however, the situation is not very different from those countries where mortality rates have increased significantly due to the health and environmental conditions and the economic embargo that lasted from 1990 to 2003 and the consequent lack of food and basic medical supplies and wars that left many epidemics and diseases and As well as the political and security instability since the US invasion of Iraq in 2003 till the recent time. All these factors have had a clear effect on the growth of children mortality. Therefore, there was necessary to study deeply to analyze this phenomenon on scientific and statistical basis, enabling the health authorities and organizations concerned with children Protection to adopt a methodology and plans to reduce this phenomenon in order to preserve the future of our generations and to promote a healthy reality to build a healthy society[11]. In this study, linear regression models (simple, quadratic and cubic) will be used to analyze mortality data and to compare the mortality rates of the age groups under study with height and explanatory power indicates and the acceptability of each model in the interpretation of mortality.